To find the x-intercepts, we need to set y equal to zero and solve for x.
1. $y = (x+4)(x-1)$
Setting y = 0:
$0 = (x+4)(x-1)$
$x+4 = 0$ or $x-1 = 0$
$x = -4$ or $x = 1$
Therefore, the x-intercepts are -4 and 1.
2. $y = -(x-3)(x+3)$
Setting y = 0:
$0 = -(x-3)(x+3)$
$x - 3 = 0$ or $x + 3 = 0$
$x = 3$ or $x = -3$
Therefore, the x-intercepts are 3 and -3.
3. $y = -(x-2)(x+6)$
Setting y = 0:
$0 = -(x-2)(x+6)$
$x - 2 = 0$ or $x + 6 = 0$
$x = 2$ or $x = -6$
Therefore, the x-intercepts are 2 and -6.
4. $y = -(x-5)(x-6)$
Setting y = 0:
$0 = -(x-5)(x-6)$
$x - 5 = 0$ or $x - 6 = 0$
$x = 5$ or $x = 6$
Therefore, the x-intercepts are 5 and 6.
Find the X intercepts of each relation without graphing: Y=(x+4)(x-1) , y=-(x-3)(x+3) , y=-(x-2)(x+6) , y=-(x-5)(x-6)
1 answer